1997
DOI: 10.1038/39622
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-binding protein is required to combat a murine Gram-negative bacterial infection

Abstract: An invading pathogen must be held in check by the innate immune system until a specific immune response can be mounted. In the case of Gram-negative bacteria, the principal stimulator of the innate immune system is lipopolysaccharide (LPS), a component of the bacterial outer membrane. In vitro, LPS is bound by lipopolysaccharide-binding protein (LBP) and transferred to CD14--the LPS receptor on the macrophage surface--or to high-density lipoprotein (HDL) particles. Transfer to CD14 triggers an inflammatory res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
237
2
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 334 publications
(253 citation statements)
references
References 17 publications
13
237
2
1
Order By: Relevance
“…LPS-BP is essential for rapid induction of an inflammatory response when a small amount of LPS is present. Recent studies have generated new insight into LPS kinetics and suggest a protective role of LPS-BP (21), contrary to previous beliefs (20,56). The significant upregulation of LPS-BP in male rats and the opposite trend in female rats may suggest greater susceptibility of female sex to inflammatory effects of chronic ethanol consumption and may help explain the previous observation that alcohol-induced liver injury in females develops more quickly and after less amount of alcohol (19,31,38).…”
Section: Gene With Changed Expression In Both Sexes Of Ethanol-fed Ratscontrasting
confidence: 52%
“…LPS-BP is essential for rapid induction of an inflammatory response when a small amount of LPS is present. Recent studies have generated new insight into LPS kinetics and suggest a protective role of LPS-BP (21), contrary to previous beliefs (20,56). The significant upregulation of LPS-BP in male rats and the opposite trend in female rats may suggest greater susceptibility of female sex to inflammatory effects of chronic ethanol consumption and may help explain the previous observation that alcohol-induced liver injury in females develops more quickly and after less amount of alcohol (19,31,38).…”
Section: Gene With Changed Expression In Both Sexes Of Ethanol-fed Ratscontrasting
confidence: 52%
“…Another new study showed that mice deficient in the LPS binding protein had reduced capacity to combat an i.p. inoculum of Salmonella typhimurium compared with wild-type mice (33). These previous results as well as the studies described herein comprise a body of data that emphasize the importance of LPS signaling in initiating host defense mechanisms against Gram-negative bacterial infections.…”
Section: Discussionmentioning
confidence: 59%
“…15 Analysis of LBP-deficient mice showed that LBP was essential for the rapid induction of an inflammatory response by low concentrations of LPS or gram-negative bacteria. 43 As expected, LPS-induced NF-B activation in activated human HSCs was dependent on the presence of serum, a source of LBP.…”
Section: Discussionmentioning
confidence: 86%